Цивільно-правовий захист постраждалих осіб від домашнього насильства в Україні та країнах Європи - Науменко, М. В.; Naumenko, M. V. (Право і суспільство. - 2023. - № 3. - С. 117-123, 2023)
Розглянуто особливості цивільно-правового захисту постраждалих осіб від домашнього насильства в Україні та країнах Європи, досліджено правову систему захисту жінок від домашнього насильства як сукупність різноманітних механізмів, з метою виявлення причин та ефективних шляхів боротьби з ним.

The article analyzes the issue of civil law protection of victims of domestic violence: from the analysis of the genesis of the very concept of "violence" to the civil law mechanism of protection of women against domestic violence. After all, in our country, for a long time, the problem of domestic violence was not considered by society or the state, as it was considered a private matter of each family, unacceptable to raise in general. This situation was widespread for a long time in Ukraine and in the world, until it reached the level of a large-scale problem. In order to further determine the ways of protection against domestic violence, an urgent issue is to study the genesis of the causes of domestic violence through the study of scientific, historical, legislative sources on the territory of modern Ukraine, because the occurrence of any phenomenon is determined by the factors that give rise to it. Today, there is no single approach to the definition of "domestic violence" and "violence in the family", both in Ukraine and in foreign countries, although the main essence of the definitions is similar – it is the commission of intentional actions or inactions between current and former family members with with the aim of causing damage to the physical and mental health of the victim. The article examines the mechanism of civil law protection of women against domestic violence, classifying forms of protection as jurisdictional (suitable) and non-jurisdictional (non-suitable). Every person has the right to apply to the court for the protection of his personal or property right and interest (Part 1, Article 16 of the Civil Code). A person has the right, at his own discretion, to choose between jurisdictional (summons) protection and non-jurisdictional (non-summons) protection. Various forms of protection can be combined to achieve the most effective protection of the rights of subjects. For the effective work of domestic legislation in the fight against domestic violence, it is advisable to study and adapt foreign experience in the field of protecting women from domestic violence, and for this a comprehensive scientific analysis is required, the obtained results require professional adaptation to national specifics, improvement of the legal framework in this area and implementation mechanism.

Рассмотрены особенности гражданско-правовой защиты пострадавших от домашнего насилия в Украине и странах Европы, исследована правовая система защиты женщин от домашнего насилия как совокупность различных механизмов, с целью выявления причин и эффективных путей борьбы с ним.
Civil and legal protection of victims from domestic violence in Ukraine and European countries
Keywords: насильство; violence; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; домашнє насильство; domestic violence; домашнее насилие; цивільно-правовий захист; civil protection; гражданско-правовая защита; зарубіжний досвід; foreign experience; зарубежный опыт; Україна; Ukraine; Украина